A Scenario Study of Investment: Portfolio Modeling Through Simulation on Virtual Management Funding Corporation - Suryawati, Baiq Nurul (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2017)
This investment scenario study was created with the help of a virtual company engaged in investment management, called UoM Fund Management Corportation. The simulation with the establishment of this virtual company will facilitate the application and understanding of various portfolio theory and modeling. It is recommended to investors to divide their investment activities into three categories, Strategy Determinants (Team S), Alpha or Advantage (A) Finders, and Quantitative Research Assessors (Q). This division of activities is expected to maximize the profits of investors.